Influence of finishing/polishing on color stability and surface roughness of composites submitted to accelerated artificial aging - Gustavo Da Col dos Santos Pinto; Kleber Campioni Dias; Diogo Rodrigues Cruvinel; Lucas da Fonseca Roberti Garcia; Simonides Consani; Fernanda de Carvalho Panzeri Pires- (Wolters Kluwer Medknow Publications, 2013)
Aim: To assess the influence of finishing/polishing procedure on color stability (ΔE ) and surface roughness (Ra ) of composites (Heliomolar and Tetric - color A2) submitted to accelerated artificial aging (AAA). Materials and Methods : Sixty test specimens were made of each composite (12 mm × 2 mm) and separated into six groups (n = 10), according to the type of finishing/polishing to which they were submitted: C, control; F, tip 3195 F; FF, tip 3195 FF; FP, tip 3195 F + diamond paste; FFP, tip 3195 FF + diamond paste; SF, Sof-Lex discs. After polishing, controlled by an electromechanical system, initial color (spectrophotometer PCB 6807 BYK GARDNER) and Ra (roughness meter Surfcorder SE 1700, cut-off 0.25 mm) readings were taken. Next, the test specimens were submitted to the AAA procedure (C-UV Comexim) for 384 hours, and at the end of this period, new color readings and R a were taken. Results: Statistical analysis [2-way analysis of variance (ANOVA), Bonferroni, P < 0.05] showed that all composites demonstrated ΔE alteration above the clinically acceptable limits, with the exception of Heliomolar composite in FP. The greatest ΔE alteration occurred for Tetric composite in SF (13.38 ± 2.10) statistically different from F and FF (P < 0.05). For Ra , Group F showed rougher samples than FF with statistically significant difference (P < 0.05). Conclusion: In spite of the surface differences, the different finishing/polishing procedures were not capable of providing color stability within the clinically acceptable limits.